PENENTUAN SIFAT MAGNETIK PASIR DAN DEBU SEPANJANG JALAN KARTAMA KOTA PEKANBARU MENGGUNAKAN MAGNETIC PROBE PASCO PS-2162 - Maria Sonya Nauli Nainggolan; Erwin Erwin; Yanuar Yanuar; Usman Malik (Universitas Riau, 2019)
Topsoil is the recipient of various kinds pollutants, especially heavy metals. Heavy metals have been detected in sand and dust along the highway. Measuring the magnetic properties of road sediment along Kartama road in Pekanbaru City has been done. The magnetic properties measured are magnetic degree, magnetic and mass susceptibility using magnetic induction measurement. The Samples were taken at sixteen locations with the amount of 1 or 2 kg for each point location, the samples were named as samples 16, 7a7e, 8a8e. The magnetic particles of the samples were separated from sand and dust using Iron Sand Separator and later using Neodymium Iron Boron (NdFeB) magnet. The total magnetic induction of the samples and concentrates were measured using Pasco Magnetic Probe PS-2162. In order to measure the magnetic induction of the samples, a solenoid of 3 cm in diameter, length of 10 cm and 2000 of windings was made. The empty solenoid magnetic induction was measured as a function of applied current ranging from 210 A and as a function of horizontal distance of 15 mm from the the solenoid ends. Total magnetic induction (samples and concentrates) was measured for the applied currents of 6 A. The results showed that the highest magnetic degree obtained from the sample number 7e that is 2.54% and the lowest level obtained from the sample number 3 that is 0.17%. The highest magnetic susceptibility value obtained from the sample number 7b was is 9158.12 , and the lowest magnetic susceptibility value obtained from the sample number 2 with the value of 3125.52 . Based on the mass susceptibility values of the concentrate obtained that the sand and dust along the road Kartama Pekanbaru which are in the interval 4.6 to 8.0, they implies that the mass susceptibility of the samples is in the range of Ilmenite phase FeTiO3or antiferromagnetic.